Information support of CAD of technological processes of structurally complex product prototypes - A. V. Petukhov (Informatika)
Objectives. The purpose of the study of information support for computer-aided process planning system of prototypes of structurally complex products is to formalize the adoption of technological decisions using interconnected databases.Methods. The method of decomposition of technology design processes was used in the work.Results. In the study of information support for computer-aided process planning system of prototypes of structurally complex products, the problem of determining the structure of information support was solved, the sequence of using information support at various stages of system implementation was determined and universal scheme for the formation of operational description of the technological process was developed.Conclusion. The use of the results of the study in the creation of computer-aided process planning system for prototypes of structurally complex products could increase the productivity of technological design in 7.8 times.